(untitled) (International journal of artificial intelligence, 2026)
Emotional intelligence (EI or EQ) encompasses the ability to recognize, understand, manage, and use emotions effectively in oneself and others. In early childhood education (ECE), fostering EI is foundational for children's cognitive, social, emotional, and academic development. This article explores the critical role of EI in ECE through a comprehensive review of theoretical frameworks, empirical evidence, and practical strategies. It highlights how high EI correlates with better academic outcomes, stronger peer relationships, reduced behavioral problems, and long-term mental health benefits. The paper draws on international research, including contributions from Daniel Goleman and Mayer-Salovey models, alongside Uzbek educational contexts and studies. A mixed-methodology approach synthesizes literature and references practical interventions. Findings underscore that investing in EI during the preschool years (ages 3-7) yields substantial societal returns by promoting resilient, empathetic, and successful learners. Recommendations for educators, parents, and policymakers in Uzbekistan and globally emphasize integrating structured SEL (Social-Emotional Learning) programs into ECE curricula.